Effect of School Based Management on Teacher Job-Satisfaction and Job-Performance - Wesly Hutabarat (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. Introduction of Weber’s organizational structure into Indonesian Educational system since the Dutch colonial resulted in a difficult time. The use of Weber ‘s organizational structure had made it difficult for teachers to make decisions concerning with schools facilities, curriculum, and student recruitment. The school principals usually had to wait for sometimes from their superintendents to make decisions concerning with school facilities, curriculum and student recruitments. Introduction of School based management into Indonesian Educational system since 2003 has made a great impact on teacher job satisfaction and job-performance. Recent studies showed that 57.30% of school based management directly contributed to job satisfaction and indirectly 11.10% contributed to job satisfaction through work motivation. Further investigation reported that total effect of school based management toward job-satisfaction and job-performance were 48.4% and 30.8% respectively. It was concluded that school based management contributed a great impact on teacher job-satisfaction and job-performance. Key words: job-performance, job-satisfaction, school based management